Peran Forum Anak Makassar Sebagai Agen Pelopor dan Pelapor di Kota Makassar - Iwan, Nur Annisa; Said, Irwanti; BM, St. Aisyah (Universitas Islam Negeri Alauddin Makassar, 2025)
The main issue in this research is: 1) The Role of the Makassar Children's Forum as a Pioneer and Reporter Agent. 2) The Effectiveness of the Children's Forum as a Pioneering Agent and Rapporteur. This research is qualitative with a sociological approach, using primary and secondary data sources collected through observation, interviews, and documentation. Then the data processing and analysis techniques The process is carried out in three stages, namely: data reduction stage, data presentation stage, and data verification stage or drawing conclusions. The research results show that the Role of the Makassar Children's Forum as a Pioneer and Whistleblower Agent in Makassar City includes:1) The Makassar Children's Forum plays an important role as a pioneer agent and reporter in realizing the welfare of children and creating a child-friendly environment. As a pioneering agent, they initiate programs related to education, health, protection, and children's rights, as well as influencing policies related to violence and gender equality. As a reporting agent, they voiced children's rights by reporting violations such. as violence or exploitation to the authorities. Overall, the Makassar Children's Forum contributes greatly in creating positive changes and increasing public awareness of children's issues. 2) Makassar Children's Forum successfully involved its members in programs that had a positive impact on the community, as seen in the activities at the GTC Mall. Despite facing challenges such as negative stigma, time constraints, and personal data protection, the high dedication of members still drives the continuity of this forum. The role of an effective facilitator also contributes to this success. This forum continues to strive to overcome obstacles and is committed to creating better social changes and supporting a safe environment for children in Makassar. The implication of this research is that the Makassar Children's Forum needs to be more actively involved in policy planning related to children's rights, both at the city and provincial levels, through training and workshops to strengthen their role in advocating for children's rights. Collaboration with educational institutions, non-governmental organizations, and the private sector is also important for education and awareness programs. The Makassar City Government must provide greater support through budgets and policies that support the role of the Children's Forum, while the community and families need to be encouraged to support the forum's activities and report violations of children's rights.